2010
DOI: 10.1002/ptr.3210
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP‐activated protein kinase on human gastric cancer cells by apoptosis induced by corosolic acid isolated from Weigela subsessilis

Abstract: Corosolic acid is one of the triterpenoids present in the leaves of Weigela subsessilis. The antidiabetic activity of corosolic acid has been reported previously, but to date, the anticancer effects on gastric cancer have been poorly studied. In this study, corosolic acid showed growth inhibition on SNU-601 human gastric cancer cells, with an IC₅₀ value of 16.9 ± 2.9 μM. Corosolic acid also triggered the activation of caspase-3 and poly (ADP-ribose) polymerase, while it was recovered by Z-VAD-FMK. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…Recently, different groups including us [38] have demonstrated that AMPK is an important regulator for cell apoptosis [39], [40], [41], [42], [43], [44].This serine/threonine kinase is originally thought to act as a cellular energy sensor by stimulating ATP-producing catabolic pathways and inhibiting ATP-consuming anabolic pathways [45], [46]. We and others proved that sustained AMPK activation could also promote cell apoptosis by regulating its downstream signals, including JNK [47], [48], [49], p38 [50], [51], p53 [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different groups including us [38] have demonstrated that AMPK is an important regulator for cell apoptosis [39], [40], [41], [42], [43], [44].This serine/threonine kinase is originally thought to act as a cellular energy sensor by stimulating ATP-producing catabolic pathways and inhibiting ATP-consuming anabolic pathways [45], [46]. We and others proved that sustained AMPK activation could also promote cell apoptosis by regulating its downstream signals, including JNK [47], [48], [49], p38 [50], [51], p53 [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the MeOH extract of the aerial parts of W. subsessilis contains triterpenoids such as corosolic acid, which has been shown to exhibit strong ARI effects. Corosolic acid has a structure that is closely related to those of other known ARIs, such as ganoderic acid C2 and ganoderenic A [19,20,21]. These related studies support that W. subsessilis contains ARIs.…”
Section: Resultssupporting
confidence: 54%
“…Lee et al () have conducted several studies on the ability of corosolic acid to induce cell cycle arrest and programmed cell death in human gastric cancer cells. In one gastric cancer cell line, corosolic acid was shown to act by activation of AMP‐activated protein kinase and caspase‐3, leading to programmed cell death.…”
Section: In Vitro Studiesmentioning
confidence: 99%